What’s a term? An attempt to define the term within the theoretical framework of text linguistics - Collet, Tanja (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In texts for specific purposes, terms adopt a behaviour which is contrary to the prescriptive demands of traditional terminology. Indeed, they exhibit variability both on the level of their meaning content and on the level of their linear structure. Their meaning contents are not fixed, but may be changed by the language user’s verbal and non-verbal activities. Their linear structures are not fixed, but can be adjusted to the cha racteristics of their linguistic environment, specifically the sentence or sequence of sentences in which they are being used. Examined within the framework of text linguistics, it becomes clear that this variability con- tributes to two basic characteristics of any body of sentences which constitutes a text, namely text coherence and text cohesion. Consequently, the aim of this article is to propose a new definition of the term, a definition which underscores the role the term plays in bringing about texture in texts for specific purposes.